The policy implementation of law no. 33 of 2014 concerning halal product guarantees (UU JPH) for micro-small businesses in the food and beverage sector in Surabaya city - Akbari, Ozie Karunia; Sahab, Ali; Fitrianto, Hari; Widjayanto, Febby Risti; Naufal, Adam Mochammad (Universitas Airlangga, 2024)
Micro and small enterprises (MSEs) are a sector that is important to the country's economy. Despite the limited resources, MSEs have resilience to economic crises. This research focuses on a policy implementation study of Law No. 33 of 2014 concerning Halal Product Guarantee (JPH Law) on micro and small scale businesses in the food and beverage in Surabaya City. This research raises two problem formulations, the role played by stakeholders in this law to increase halal certificates of micro small businesses in the food and beverage in Surabaya City and the obstacles faced by stakeholders in increasing halal certificates of micro small businesses in the food and beverage in Surabaya City. Researchers used the theory of policy implementation initiated by Merilee S. Grindle. This research uses descriptive qualitative methods and uses direct observation and interviews with various sources to obtain primary data. Secondary data are obtained through searches from various sources. The result of this research is that are three kinds of stakeholder actors in the implementation of the JPH Law, government, non- government institutions, and micro and small business actors in Surabaya City. Government and non-government institutions in Surabaya City organize various kinds of collaboration programmes in order to implement the JPH Law in Surabaya City. However, the implementation of the JPH Law in Surabaya City has encountered many obstacles due to weaknesses in the content of policy and context of implementation of the JPH Law that is not in accordance with the needs of the society. Keywords: Policy Implementation, Halal Certification, Socialization, Halal Product Guarantee